2016
DOI: 10.7824/rbh.v15i3.482
|View full text |Cite
|
Sign up to set email alerts
|

Subdoses de glyphosate não reduzem a produtividade da cultura do milho

Abstract: Resumo -Na aplicação de herbicidas, utilizados como maturadores, deve ser levado em consideração as culturas cultivadas em áreas adjacentes, devido ao risco de ocorrência de deriva desses produtos. Partindo do pressuposto da sensibilidade da cultura do milho ao glyphosate, objetivou-se avaliar o efeito de subdoses de glyphosate na cultura do milho quando aplicadas em estádios de desenvolvimento V4 e V8. O experimento foi instalado em Jataí, GO, constituído de 10 tratamentos estabelecidos no delineamento com bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The results showed that the maize hybrid SYN 7G17 is not selective to sulfometuron-methyl sub-doses as it is for sub-doses of ethephon and glyphosate (Felisberto et al, 2015(Felisberto et al, , 2016. Pr>Fc, probability > calculated F. VC variation coefficient.…”
Section: It Is Recorded Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the maize hybrid SYN 7G17 is not selective to sulfometuron-methyl sub-doses as it is for sub-doses of ethephon and glyphosate (Felisberto et al, 2015(Felisberto et al, , 2016. Pr>Fc, probability > calculated F. VC variation coefficient.…”
Section: It Is Recorded Onmentioning
confidence: 99%
“…Similarly to other cultures (Correia and Leite, 2012;Correia and Vilella, 2015), maize culture is subjected to drifting risk or application errors of products such as ripeners (Felisberto et al, 2016). In this context, starting from the possible sensitivity of the maize culture to sulfometuronmethyl, the goal was to evaluate the effect of sub-doses of sulfometuron-methyl on maize culture when applied at the development stages V4 and V8.…”
Section: Introductionmentioning
confidence: 99%
“…Weed management with herbicide application is fundamental for agriculture, prioritizing the rapid and vigorous initial development of the crop of productive interest (5) . Drift caused by application errors or the action of wind in dragging the glyphosate mist to other areas may cause an unintended stimulatory effect when low doses are absorbed by the plant (6) . Drift to non-target crops can lead to a productive stimulus or qualitative (as reported in protein (7) , lignin (8,9) , and sugars (10) ) and quantitative (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…O manejo das plantas daninhas com aplicação de herbicida é fundamental à agricultura, priorizando o desenvolvimento inicial rápido e vigoroso da cultura de interesse produtivo (5). Quando ocorre deriva, por erros durante a aplicação, ou pela ação do vento e arraste de névoa do glifosato para outras áreas, pode parecer efeito estimulatório involuntário, sob absorção de baixas doses na planta (6) . A deriva em cultivos não alvos pode apresentar estímulo produtivo ou alterações nas plantas de forma qualitativa, como teores de proteína (7) , lignina (8,9) , açúcares (10) , ou; quantitativa, como altura (11) , comprimento de folhas e raízes (12) , caracterizando o efeito denominado hormese.…”
Section: Introductionunclassified